Suxamethonium-Induced Prolonged Apnoea: A Clinical Case Study - Azam, Md Fakhrul; Rahman, S M Tauhidur; Debashis Chakraborty; Mohammad Faysal Howlader; Hasan, Md Nazmul (Eastern Medical College Journal, 2026)
Suxamethonium (succinylcholine) is a depolarizing neuromuscular blocking agent widely used for rapid induction of anaesthesia due to its fast onset and short duration of action. However, in rare cases, its impaired metabolism may lead to prolonged apnoea, often due to pseudocholinesterase deficiency or other metabolic factors. We report a case of a 13-year-old male patient who developed unexpectedly prolonged apnea after receiving suxamethonium during appendicectomy operation. This case highlights the importance of recognizing pseudocholinesterase deficiency in patients with prolonged neuromuscular blockade after suxamethonium. Factors such as genetic variants, liver dysfunction, or exposure to cholinesterase inhibitors may contribute to this adverse effect. Early recognition and supportive management are crucial to preventing complications. Routine preoperative screening may not be practical, but a high index of suspicion is necessary in at-risk individuals or in cases of unexplained delayed recovery. Eastern Med Coll J. July 2025; 10 (2): 143-145